2021
DOI: 10.1002/jmv.27257
|View full text |Cite
|
Sign up to set email alerts
|

Severe cytomegalovirus disease with encephalitis after CAR‐T cell therapy: A rare but potentially fatal complication

Abstract: Cytomegalovirus (CMV) is a ubiquitous herpes virus that develops lifelong latency following primary infection and can be reactivated following immune suppression.CMV encephalopathy has been described in few reports after hematopoietic stem cell transplantation and in patients with acquired immunodeficiency syndrome. To the best of our knowledge, CMV encephalopathy following CAR-T cells infusion had not been previously reported. Initial CMV viral load and monitoring are crucial in patients with CAR-T cells to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The incidence and clinical significance of CMV reactivation after CART therapy is not well described. CMV viremia (N=14) and end organ disease (pneumonitis (N=2), enteritis (N=1), encephalitis (N=2), and retinitis (N=1)) have been reported after CART therapy [4][5][6][7][8][9][10][11][12] . Another study reported that 10/60 (17%) CMV seropositive and -negative patients receiving CART therapy developed CMV reactivation based upon a single test performed from day+14 to +21 after CART infusion 13 ; none of these patients developed CMV organ disease.…”
mentioning
confidence: 99%
“…The incidence and clinical significance of CMV reactivation after CART therapy is not well described. CMV viremia (N=14) and end organ disease (pneumonitis (N=2), enteritis (N=1), encephalitis (N=2), and retinitis (N=1)) have been reported after CART therapy [4][5][6][7][8][9][10][11][12] . Another study reported that 10/60 (17%) CMV seropositive and -negative patients receiving CART therapy developed CMV reactivation based upon a single test performed from day+14 to +21 after CART infusion 13 ; none of these patients developed CMV organ disease.…”
mentioning
confidence: 99%
“…112 Thus, while the incidence of CMV viremia may be underestimated, the clinical relevance of these events remains unclear with most patients improving, even without preemptive antiviral therapy. Cases of CMV end-organ disease have been described, 36,38,111,[113][114][115][116] but are overall rare considering the widespread use of CAR-T-cell therapy in the United States and globally. However, few studies have evaluated CMV viremia in a systematic fashion in this population and the clinical relevance of asymptomatic reactivation remains unknown.…”
Section: Cytomegalovirusmentioning
confidence: 99%